Prevalence of coronary artery disease in a sample of young Egyptian population based on CT coronary angiography findings - Ahmed Hamdy Abdelghany; Mohammed Raafat Abd El-Mageed; Ahmed Shehata Mohamed Ismail; Safaa Ibrahim Saif El-nasr (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Coronary artery disease (CAD) persists among the major causes of mortality globally. In general, CAD is regarded as prevalent in older individuals. The frequency of CAD in young individuals and its risk factors are still being investigated.Traditional risk factors like hypertension, diabetes mellitus, smoking, and family history of previous coronary artery disease appear to be just as significant in younger individuals with CAD as they are in older patients. Coronary computed tomography angiography (CCTA) is a noninvasive imaging method used for examining the coronary arteries. Our study aimed to show the prevalence of CAD in the young Egyptian population based on CCTA and to highlight the different risk factors for CAD in such group. Methods we performed retrospective analysis of 227 young subjects with low to intermediate pre-test likelihood for coronary arterial disease who underwent CCTA. Presence and degree of CAD were evaluated as well as the risk factor contributing to it. Results Prevalence of CAD among the young Egyptian population (less than 40 years old) was 21.6% as detected by CCTA. Age, weight, male sex, smoking, and family history were the key risk factors for the occurrence of CAD. Conclusion CAD is prevalent among young Egyptians with almost the same risk factors as those in older population. Identifying this young population at risk is crucial for ensuring better prevention and well-being for the individual and the whole society.